ANALISIS IMPLEMENTASI DIGITAL BANKING DALAM PENINGKATAN KUALITAS LAYANAN PADA NASABAH BANK SYARIAH INDONESIA (BSI) KCP SAMARINDA - Nugraha, Muhammad Agung Nugraha; Norvadewi, Norvadewi; Noni, Yovanda (Journal of Information Systems Management and Digital Business, 2024)
The background to this research is that rapid technological developments have brought changes to product and service innovation at Bank Syariah Indonesia. Digital banking services are currently being developed to improve the quality of Bank Syariah Indonesia's services. The various conveniences and benefits provided through this digital banking service include ease of transactions, time efficiency and flexibility. However, there are still many people who have not switched to digital banking services due to a lack of understanding of the operation or not knowing about digital banking services. The objectives of this research are: 1) To determine and describe the implementation of digital banking in improving the quality of service to the community at Bank Syariah Indonesia KCP Samarinda Bung Tomo. 2) To find out and describe the obstacles and solutions to the Implementation of digital banking in improving the Quality of Service to the Community at Bank Syariah Indonesia KCP Samarinda Bung Tomo. The research method used in this research is field research using a descriptive approach. Determining informants using purposive techniques. Data collection was carried out using observation, interviews and documentation techniques. The research subjects were employees and customers of BSI KCP Samarinda Bung Tomo. Data analysis uses data reduction methods, data presentation, and drawing conclusions. Validity is carried out by source triangulation. The results of the research are: 1) The implementation of digital banking at Bank Syariah Indonesia KCP Samarinda Bung Tomo has been going well and is able to improve service quality by implementing five dimensions of service quality, namely reliability, the ability to provide fast and accurate service, responsiveness, the ability to respond quickly to customer requests. and responsiveness, assurance provides a sense of trust and security, empathy provides friendly service and tangible evidence provides the BSI Mobile application and ATM machines. 2) Obstacles to implementing digital banking include failed transactions due to the internet network. The solution is to ensure the internet network is good so that the transaction process can run smoothly. Activation failed because you didn't have credit, make sure you have credit available to avoid failure. Make sure the BSI Mobile application is updated so you can log in. Can't log in because the server has an error, the solution is to wait for information from the bank and the server will be repaired so that the application can be used normally again.